Perceived Social Support as a Predictor of Parental Self-Efficacy among Mothers of Preschool Children - Chici Firdha Azzahra Rusdyawan; Fivi Nurwianti (Journal of Educational, Health and Community Psychology, 2026)
This study examined the association between perceived social support and parental self-efficacy (PSE) among mothers of preschool-aged children (3–6 years). A quantitative cross-sectional design was employed involving 250 mothers who completed the Multidimensional Scale of Perceived Social Support and the Tool to Measure Parenting Self-Efficacy. Linear regression analysis showed that total perceived social support was significantly associated with parental self-efficacy and explained 16.8% of its variance. Further analysis across support sources revealed that family support showed the strongest positive association with parental self-efficacy, followed by support from significant others. In contrast, friend support demonstrated a more complex pattern, showing a positive bivariate association with parental self-efficacy but a negative coefficient in the multiple regression model after controlling for other support sources. This finding should therefore be interpreted cautiously, as it may reflect shared variance among support dimensions rather than a direct negative relationship. Overall, the findings indicate that perceived social support is not a homogeneous construct in relation to parental self-efficacy, as different sources of support may contribute through distinct relational and psychological pathways.